2010
DOI: 10.1007/s00404-010-1728-2
|View full text |Cite
|
Sign up to set email alerts
|

Iron status parameters in preeclamptic women

Abstract: We recommend that any pregnant female with higher serum iron and ferritin concentrations should be further investigated for preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 30 publications
4
31
0
1
Order By: Relevance
“…The answer is almost certainly that it is a leakage molecule from damaged cells (126), and when in serum it is found to have lost its iron content (782785). Serum ferritin is, as expected, raised during PE (244, 246, 249, 253, 255, 786, 787) and in many other inflammatory diseases (126), including infection [e.g., Ref. (788, 789) and above].…”
Section: Proteomic and Similar Biomarkers – Circulating And Placentalsupporting
confidence: 74%
“…The answer is almost certainly that it is a leakage molecule from damaged cells (126), and when in serum it is found to have lost its iron content (782785). Serum ferritin is, as expected, raised during PE (244, 246, 249, 253, 255, 786, 787) and in many other inflammatory diseases (126), including infection [e.g., Ref. (788, 789) and above].…”
Section: Proteomic and Similar Biomarkers – Circulating And Placentalsupporting
confidence: 74%
“…There was highly significant difference of mean serum ferritin concentration between cases and controls (p = 0.0001) ( Table -I). The study also showed that mean serum accordance with other similar studies like Rayman et al 6 Recent study by Siddiqui et al 8 also revealed that serum ferritin and serum iron concentration were significantly higher (p<0.05) in preeclamptic women in comparison to normal pregnant women which are similar to the findings of present study. However, Ugwaja et.…”
Section: Resultssupporting
confidence: 83%
“…However, endothelial dysfunction has been considered to play a central role in the pathophysiology of preeclampsia 5 . In many studies alteration of iron status has been claimed as a factor for vascular endothelial cell damage of preeclampsia and its consequences [6][7][8] . Iron is essential to nearly all cells but the amount of iron required by Bangladesh J Med Biochem; 5 (2) 54 R Sultana, S Ahmed, N Sultana, SM Fazlul Karim et al iron concentration in cases was 121.78±41.93 µg/dl and that in controls was 61.04±24.18 µg/dl.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Siddiqui et al 28 , mean serum ferritin concentration in preeclamptics was higher than in normal pregnant women. In this study, no significant differences were found among hemoglobin concentration or hematocrit, either.…”
Section: Discussionmentioning
confidence: 81%